Genetic parameters and validation of microsatellite markers associated with iron and zinc in common bean - Carloni, Poliana Regina; de Souza, Thiago Lívio Pessoa Oliveira; de Aguiar, Marcelo Sfeir; Melo, Leonardo Cunha; Melo, Patrícia Guimarães Santos; Pereira, Helton Santos (Empresa Brasileira de Pesquisa Agropecuária, 2023)
The objective of this work was to estimate the genetic parameters, evaluate the agronomic performance, and validate the microsatellite molecular markers (SSRs) linked with quantitative trait loci (QTLs) for Fe and Zn concentrations in grains of common bean, in order to select superior lines. One hundred and sixteen lines from two populations ('BRS Requinte' × 'Porto Real' and 'BRS Requinte' × G2358) and five check genotypes were evaluated in three environments. The parents and lines were genotyped with 20 SSRs. In the simultaneous selection of the lines for the four evaluated traits, the gains from selection were 4.7% for Fe concentration, 2.8% for Zn concentration, 3.9% for yield, and 0.9% for 100-seed weight. Therefore, there is the possibility of selection of lines that combine desirable phenotypes for the traits of interest. The only polymorphic marker is BM 154 in the 'BRS Requinte' × 'Porto Real' population, indicating that the QTLs linked with the markers may already be fixed or that the markers are not associated in the used populations. The single-marker analysis of QTL mapping shows an association between BM 154 and Fe concentration in only one environment, explaining 14.5% of phenotypic variation, which indicates the occurrence of the interaction of QTLs with environments.